Structural characteristics of plankton community in Dongting Lake and its relationship with water environmental factors - Hong Yuan; Yaqin Xiao; Yuanyuan Xie; Huahui Luo; Jingyi Liu; Jialuan Xu; Xiaoli Wu; Dunxue Chen; Yandong Niu (Scientific Reports, 2024)
Abstract The plankton community structure and environmental factors in Dongting Lake were investigated during four seasons from September 2020 to August 2021. The results revealed 147 species from 58 genera and 7 phyla of phytoplankton and 84 species from 56 genera and 4 phyla of zooplankton in Dongting Lake. The characteristics of plankton communities varied with time and space. The temporal variation of phytoplankton abundance ranged from 43.5201 × 104 to 120.7968 × 104 cells/L and the spatial variation ranged from 18.6707 × 104 to 247.5542 × 104 cells/L. The temporal variation of zooplankton abundance ranged from 18 to 42 ind/L and the spatial variation ranged from 19 to 62 ind/L. The temporal and spatial variations of the abundance range values were much larger for phytoplankton than for zooplankton, with phytoplankton dominating. However, environmental factors in Dongting Lake vary more temporally than spatially, and drive more temporal than spatial variations in planktonic organisms. Based on the redundancy analysis WT, DO, and CODMn were the main environmental factors affecting the distribution of phytoplankton, while WT, CODMn, NO2–N, and Chl-a were the main factors affecting the distribution of zooplankton. WT and CODMn were the common key influencing factors.